ATRT-19. Functional genomics reveal distinct modulators of response to CDK4/6 inhibitors in ATRTs. (3rd June 2022) - Merk, Daniel; Hirsch, Sohpie; Tsiami, Foteini; Walter, Bianca; Haeusser, Lara; Babaei, Sepideh; Admard, Jakob; Casadei, Nicolas; Roggia, Cristiana; Spohn, Michael; Schittenhelm, Jens; Singer, Stephan; et al.
Abstract: Brain tumors are the leading cause of cancer-related deaths in children, and atypical teratoid rhabdoid tumors (ATRTs) are among the most common aggressive brain tumors in infants. With no standard-of-care treatment so far, ATRTs continue to have relatively low survival estimates, illustrating the urgent need for more efficacious treatment options. We have previously used genome-wide CRISPR/Cas9 knockout screens in combination with small-molecule drug assays to identify targetable vulnerabilities in ATRTs. CDK4/6 inhibitors, among the most promising drugs in our study with direct translational potential, are capable of inhibiting tumor growth due to mutual exclusive dependency of ATRTs on either CDK4 or CDK6. We here used genome-wide loss-of-function and gain-of-function strategies to identify modulators of response to CDK4/6 inhibition in ATRTs. Of note, while some well-known resistance mechanisms such as loss of RB1 or FBXW7 are shared by ATRT cell lines, we have also identified modulators of response to CDK4/6 inhibition with opposing effects across ATRT cell lines. As such, loss of AMBRA1, a recently described master regulator of D type cyclins, can either oppose the effects of or synergize with CDK4/6 inhibitors based on the cellular background. We are currently using a proteomics approach to further delineate the mechanism driving this functional heterogeneity of AMBRA1 in ATRTs. Our study will therefore provide deeper insights into the response of ATRTs to CDK4/6 inhibitors, which represent one of the most promising class of targeted agents for the treatment of ATRTs.